Social dimensions in the lab session when novices learn to program - von Hausswolff, Kristina; Weurlander, Maria (2020 IEEE Frontiers in Education Conference (FIE), 2020)
This full research paper reports on a study of social dimensions when students learn to program. The aim of this study is to investigate students' experiences of social dimensions in learning to program as novices in a pair-programming lab setting. Data was collected by means of individual interviews with seven students mid-way through the course. A questionnaire to 77 students gave a background of the class as a whole and was used to select students for the interviews. The interview data were analyzed using an inductive content analysis method and interpreted theoretically from a pragmatist and transactional perspective on learning. Our results show different ways that the social dynamic between the students in a pair affected 1) the emotions experienced, 2) the extent to which students actively wrote code and interacted with the computer environment, and 3) how students perceived their competence. Interviewed students report that failure and success in a programming task result in an emotional roller coaster, and that in this turbulence, the social context is of utmost importance and weighs in when students consider if they are going to pursue a programming profession.